RAGAM HIAS TRADISIONAL JAWA Studi Rekonstruksi Visual Untuk Desain Kriya Kayu - Prabowo, Rahayu Adi (Brikolase : Jurnal Kajian Teori, Praktik dan Wacana Seni Budaya Rupa, 2019)
Javanese traditional ornaments are one of the richness of the archipelago's culture. A variety of craft works in the form of decorative motifs from various ethnic Archipelago has given rise to a style with its own characteristics and uniqueness. The focus of this study is to explain the traditional Javanese decorative motifs. The study of motif reconstruction as a method of developing and preserving traditional Javanese decorative motifs, as an alternative design of wood craft products.Qualitative methods and explorative experimental methods are used as a basis for analyzing and translating experimental reconstruction designs for the visual development of wood crafts in Indonesia that are Indonesian, unique and varied. The development of alternative designs with various reconstructions of traditional ornamental motifs will enrich the repertoire of traditional fine arts culture in Indonesia.